Modern architecture: a planetary warming history - Ibelings, Hans 1963- (The Architecture Observer, 2023)
"Modern architecture is inseparably linked with the Industrial Revolution. Industrially manufactured materials such as iron, steel, reinforced concrete, glass, asbestos, and later also plastics, have helped to make architecture modern. The Industrial Revolution also set planetary warming in motion. Thus, it is not far-fetched to claim that there are also correlations between modern architecture and planetary warming. This book is a rough sketch of a proposed history of modern architecture since the beginning of the Industrial Revolution. It aims to break away from the established neural networks of the profession’s collective memory of how modern architecture’s history has unfolded, and offers the beginning of a rewiring: by introducing new actors, and highlighting ideas and projects that deal with climate and environment, while relegating some of the usual stars of modernism and postmodernism to the background."--Back cover
Includes bibliographical references and index
Keywords: Geschichte 1800-2022; Erwärmung -- Meteorologie; Baustoff; Klimaänderung; Architektur; Architecture / Environmental aspects; Building materials / Environmental aspects; Global warming; Architecture - Aspect de l'environnement; Réchauffement de la Terre; global warming; Architecture - Environmental aspects; Building materials - Environmental aspects